The social welfare of women and children with HIV and AIDS legal protections, policy, and programs - Stein, Theodore J. (New York ; Oxford : Oxford University Press, 1998)
The author explores such issues as discrimination in employment, housing, health care, and education, and looks at medical testing, confidentiality, reproductive freedom, income assistance, child welfare, and child custody. He also examines the statutes that govern the operations of the public systems these people turn to.
Description based on print version record.
Includes bibliographical references and index.
Keywords: AIDS (Disease) in women -- Patients -- Legal status, laws, etc. -- United States; HIV-positive women -- Legal status, laws, etc. -- United States; Women patients -- Legal status, laws, etc. -- United States; Children of AIDS patients -- Legal status, laws, etc. -- United States; AIDS (Disease) in women -- Patients -- Services for -- United States; Women patients -- Services for -- United States